Alternative Index Ratio of Treasury Bonds - Pszczółkowska , Marta (Studia Oeconomica Posnaniensia, 2014)
Indexed bonds have been issued in Poland since 1994. Despite the positive opinions of international institutions and economists regarding such bonds, in the last decade they were issued to cover an average of less than 4% of Treasury debt. The interest rate of these bonds is composed of a fixed interest margin and a variable margin depend - ent on the inflation rate, measured by the Consumer Price Index. However, it is possible to use different reference values. The analysis presented in this paper covers the period 2005-2012 and includes four alternative solutions: inflation rate without administrative prices; inflation rate without seasonal prices; as well as GDP growth rate for seasonally adjusted and raw data series. Compared with the value of interest payments according to the current system, it can be concluded that the use of the CPI was more expensive for the state than the other four options would have been in the economic conditions during the analysed period. Other macroeconomic conditions could also influence the results but a key issue is the difficulty in predicting them.